About death and dying: a space for observation - Ferreira, Ana Maria Yamaguchi; Wanderley, Katia da Silva (Revista Kairós-Gerontologia, 2014)
This article discusses thoughts and concepts about Palliative Care and Thanatology, sciences dealing with death and the dying process subjects, aiming to widen observations, analysis and discussions already in place about the themes, aiding either the uninitiated public as health care professionals, to handle death and the dying process in a more humanized and closely way, like conditions associated to each and every human being.